Comparison of Characteristics of Neuropathic and Non-neuropathic Pruritus to Develop a Tool for the Diagnosis of Neuropathic Pruritus: The NP5 - Huguen, Johanna; Brenaut, Emilie; Clerc, Caroline-Jade; Poizeau, Florence; Marcorelles, Pascale; Quereux, Gaëlle; Dupuy, Alain; Misery, Laurent (Frontiers in Medicine, 2019)
The diagnosis of neuropathic pruritus (NP) may be difficult. The aim of this study was to compare the characteristics of both NP and non-neuropathic pruritus (NNP) in order to elaborate a tool to help the diagnosis of NP without clinical examination. 107 patients were included: 53 in the NP group and 54 in the NNP group. In multiple regression, presence of twinges, absence of burning, worsening with activity, no worsening with stress, and relief with cold ambient temperature were independent factors that were associated with NP. A score of two criteria out of five was optimal to discriminate NP from NNP with a sensitivity of 76% and a specificity of 77%. Alloknesis, hyperknesis or the ice cube test were not included because their evaluation is based on clinical examination